Flower-shaped composite wave-absorbing material with multiple heterojunction interfaces and preparation method thereof
Patent Information
- Application Number
- CN202611118980.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-09-25
AI Technical Summary
特别的,包含永磁氮化铁Fe16N2的复合吸波材料目前探究较少,其有着很大的应用前景
[0019]与现有技术相比,本发明的有益效果至少在于,氮化工艺采用传统的气体渗氮工艺,技术成熟,制备工艺简单,成本可控;通过CaH2干燥剂来降低氮化粉体表面水分压,可极大地降低氮化时间,节约时间成本和能耗;工序简单的制备了自组装多物相复合氮化物,且可充分利用制备永磁氮化铁Fe16N2过程中产生的低纯度副产物,合理将低永磁性能粉体应用于吸波领域。通过简易的工序复合了介电材料和磁性材料,获得多模式吸波效果改善吸波特性等。
Smart Images

Figure CN122823110A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of microwave absorbing functional materials, specifically relating to a flower-shaped multi-heteromeric interface dielectric material / iron nitride composite microwave absorbing material and its preparation method. Background Technology
[0002] In the information age, microwave technology is widely used in many fields and has become an important part of daily life, but it also brings a large amount of electromagnetic radiation. Absorbing materials can greatly reduce the damage caused by electromagnetic waves and have outstanding applications in fields such as stealth materials. After years of development, various types of absorbing materials have been developed and put into production, and new materials with promising applications in the field of microwave absorption are constantly being developed. Based on their main absorption principles, absorbing materials can be divided into two main categories: electrical loss type and magnetic loss type. Electrical loss type materials mainly include graphite, carbon black, and silicon carbide, while magnetic loss type materials mainly include ferrite, iron nitride, and magnetic micropowders. Among various absorbing materials, iron-based magnetic materials, which are mainly of the magnetic loss type, have high saturation magnetization, resulting in excellent magnetic loss effects. Furthermore, due to their controllable microstructure, they can achieve a certain synergistic effect between dielectric loss and magnetic loss. In recent years, due to the demand for sustainable development of rare earth resources, the development of rare earth-free permanent magnet materials has become increasingly popular among iron-based magnetic materials. This has also led to an increasing demand for the preparation of permanent magnet iron nitride materials. However, the preparation process is prone to producing low-purity multiphase composites. From the perspective of resource utilization, it is also very necessary to make reasonable use of these low-purity multiphase composite iron nitrides.
[0003] Traditional iron-based magnetic materials require a series of complex synthesis processes to obtain various composite heterostructures. However, the synthesis process of iron nitride materials can easily achieve self-assembled heterostructures. These heterostructures can introduce higher dielectric losses and magnetic losses due to the inherent magnetic properties of the iron nitride material itself. These heterostructures result in better electromagnetic wave absorption. Combining these microwave absorbing materials with rich magnetic loss characteristics with dielectric materials such as carbon and silicon carbide to achieve a composite of magnetic and electrical loss-type microwave absorbers can improve their corrosion resistance and absorption bandwidth, further expanding their application range. Specifically, materials containing permanent magnet iron nitride (Fe)... 16 There is currently limited research on N2 composite absorbing materials, but they have great application potential. Summary of the Invention
[0004] Improving the microwave absorption performance of existing microwave absorbing materials typically involves constructing heterogeneous interfaces, but multiphase composite processes are complex. Meanwhile, permanent magnet phase iron nitride (Fe)... 16The preparation of N2 materials easily produces multiphase low-purity iron nitride, which has not been well utilized. This invention aims to rationally utilize the characteristics of multiphase low-purity powder and the ease with which heterogeneous interfaces can be constructed during the nitridation process of iron nitride. Furthermore, it proposes a composite microwave absorbing material of dielectric material and iron nitride with multiple heterogeneous interfaces to further enhance the absorption properties by compositing dielectric materials with dielectric materials on the basis of magnetic materials. This composite microwave absorbing material prepares an oxide precursor by combining a dielectric material with predominantly high electrical loss and iron oxide. A dielectric material and pure iron composite nitride precursor are obtained through hydrogen reduction. Finally, by controlling the nitridation process, the pure iron in the composite is prepared into multiple self-assembled iron nitride composite phases to obtain a composite material of dielectric material and magnetic iron nitride. The magnetic coupling effect of the composite iron nitride brings good magnetic loss performance, and the multiple heterogeneous interfaces of different iron nitrides, especially the composite of dielectric materials, bring good dielectric loss performance. This gives the composite material a multi-mode electromagnetic wave loss mechanism, resulting in excellent microwave absorption performance.
[0005] The present invention adopts the following technical solution: This invention provides a method for preparing a composite microwave absorbing material with a flower-like multi-heteromeric interface, which combines a dielectric material and a magnetic iron nitride material. The specific steps are as follows: Water-soluble iron salts, urea, and dielectric materials are uniformly dispersed in a solvent, and then subjected to a high-temperature, high-pressure hydrothermal reaction in a high-pressure reactor to obtain a composite material of iron hydroxyl oxide and dielectric materials. After the reaction, the precipitate of the composite material of iron hydroxyl oxide and dielectric materials is washed with deionized water, centrifuged and dried, and then subjected to high-temperature heat treatment oxidation to obtain a composite precursor powder of dielectric materials and iron oxide. The composite precursor is a flower-like structure formed by the interlocking of dielectric materials and iron oxide through a hydrothermal reaction. The composite precursor powder is mixed with a desiccant and then reduced with hydrogen to obtain a mixture of dielectric material, pure iron composite particles, and desiccant. After complete reduction, an inert gas is used for protective cooling, followed by a low-temperature nitriding reaction to regulate the phase composition of the iron nitride. After complete nitriding, the mixture is placed in a low-oxygen atmosphere for pre-oxidation treatment in a stepwise manner to prevent the powder from undergoing severe oxidation and combustion. Finally, the desiccant and its reaction products are removed, and after drying, a self-assembled flower-like multi-heteromeric interface composite microwave absorbing material is obtained.
[0006] Preferably, a composite material of iron hydroxyl oxide and dielectric material is obtained through a high-temperature hydrothermal reaction. The reaction product is washed with deionized water, centrifuged and dried, and then subjected to high-temperature heat treatment to obtain iron oxide / dielectric material composite powder.
[0007] Preferably, the water-soluble iron salt is composed of one or two of Fe(NO3)3·9H2O and FeCl3·6H2O mixed in any proportion, and the molar ratio of iron salt to urea is 1:1~15.
[0008] Preferably, the high dielectric material used is a mixture of one or two traditional loss-type materials such as nano-SiC and carbon powder in any proportion, with the molar ratio of iron salt to dielectric material being 1:0.1~1.
[0009] Preferably, organic sugars such as sucrose and glucose that can be dehydrated and carbonized are added to the hydrothermal reaction solution. The carbon powder formed by the dehydration and carbonization of these organic sugars through hydrothermal reaction also serves as a dielectric material.
[0010] Preferably, the solvent used is ethylene glycol, water, or a mixture of ethylene glycol and water, with a volume of 400 ml, and the high-pressure reactor has a volume of 500 ml.
[0011] Preferably, the high-temperature and high-pressure reaction temperature in the reactor is 140~180 °C, and the reaction time is 10~20 h.
[0012] Preferably, the high-temperature heat treatment temperature is 300~600 °C and the time is 0.5~3 h.
[0013] Preferably, the desiccant is CaH2 or CaO powder, and the mass ratio of iron oxide to desiccant is 1:1~6.
[0014] Preferably, the reducing atmosphere is hydrogen or a mixture of hydrogen and an inert gas (helium, argon, nitrogen), the hydrogen flow rate is 200~600 sccm, the reduction temperature is 360~420 °C, and the reduction time is 2~4h.
[0015] Preferably, the inert gas used for protection and cooling is helium or argon, which do not react with the metal powder.
[0016] Preferably, the low-temperature nitriding gas atmosphere is ammonia or a mixture of ammonia and hydrogen, with an ammonia flow rate of 100~600 sccm, a hydrogen flow rate of 0~400 sccm, a temperature of 140~200 °C, and a nitriding time of 0.5~40 h.
[0017] Preferably, the oxygen content of the pre-oxidation treatment low-oxygen atmosphere is 0.05%~5%.
[0018] As a preferred method, the desiccant is first ultrasonically dispersed with anhydrous ethanol, then separated by magnetic adsorption using a magnet, and finally the desiccant and its reaction products are removed using a mixed solution of ethanol and water or NH4Cl.
[0019] Compared with existing technologies, the beneficial effects of this invention are at least as follows: the nitriding process adopts a traditional gas nitriding process, which is technically mature, simple in preparation, and cost-controllable; by using CaH2 desiccant to reduce the surface moisture pressure of the nitrided powder, the nitriding time can be greatly reduced, saving time, cost, and energy consumption; the simple process prepares self-assembled multi-phase composite nitrides, and can fully utilize the preparation of permanent magnet iron nitride (Fe). 16 The low-purity byproducts generated during the N2 process are used to rationally apply low-permanent-magnetic-performance powders to the microwave absorption field. A simple process is used to combine dielectric and magnetic materials, achieving multi-mode microwave absorption effects and improving absorption characteristics. Attached Figure Description
[0020] Figure 1 This is a process flow diagram of the preparation method of a flower-shaped multi-heterogeneous interface composite microwave absorbing material according to the present invention.
[0021] Figure 2 The nano-SiC added in Example 1 was reacted hydrothermally to obtain SiC / ferric hydroxide, and after heat treatment, SiC / Fe2O3 composites were obtained. After nitriding, SiC / ferric nitride with multiple heterogeneous interfaces (ferric nitride is composed of Fe) was obtained. 16 XRD pattern of a composite microwave absorbing material composed of N2, Fe4N and Fe.
[0022] Figure 3 The image shows a SEM image of the SiC / iron nitride composite microwave absorbing material prepared in Example 1.
[0023] Figure 4 The image shows the elemental distribution of the SiC / iron nitride composite microwave absorbing material prepared in Example 1.
[0024] Figure 5 The diagram shows the electromagnetic wave absorption performance of the dielectric material / iron nitride composite absorbing material obtained in the example.
[0025] Figure 6 The electromagnetic wave absorption performance of the dielectric material / iron nitride composite absorbing material obtained for comparison is shown in the figure. Detailed Implementation
[0026] To better utilize the preparation of permanent magnet iron nitride Fe 16 Low-purity iron nitride composite materials (composed of Fe, Fe4N, Fe3N, Fe) are easily generated during the N2 process. 16 (Two or more components of N2), and further improve its wave absorption properties. Through long-term research and extensive practice, the inventors of this case have proposed a wave-absorbing material composed of a dielectric material with multiple heterogeneous interfaces and iron nitride, and its preparation method. The main basis includes at least the following: (1) Preparation of permanent magnet iron nitride Fe by low-temperature nitriding method 16The N2 process and equipment are simple, making it more suitable for industrial production compared to magnetron sputtering and ion implantation. However, the preparation of permanent magnet iron nitride (Fe) is more complex. 16 During the N2 process, high-nitrogen compounds such as Fe4N and Fe3N phases are easily generated, leading to Fe... 16 The low purity of N2 limits the market application of its low-purity products. Moreover, the nitriding process starts from the particle surface. As ammonia gas contacts the surface of metallic Fe and catalytically decomposes to produce active nitrogen atoms, these atoms continuously diffuse chemically into the inner layer to produce nitrides. The outer layer is prone to producing high-nitrogen compounds, while the inner layer consists of low-nitrogen iron nitride or even unnitrided Fe. This is a self-assembled heterogeneous interface structure between different phases. Further preparation of composite precursors of iron oxide and dielectric materials can easily yield composites of multiple iron nitrides and dielectric materials.
[0027] (2) Iron nitride materials themselves have good electromagnetic wave absorption characteristics. For example, soft magnetic phase iron nitride Fe4N has been widely studied in the field of electromagnetic wave absorption, and even has good corrosion resistance. Permanent magnetic iron nitride Fe... 16 N2 has also been proven to have good electromagnetic wave absorption potential. Its self-assembled multiple iron nitride composites and the magnetic coupling between different iron nitrides bring better magnetic loss characteristics to electromagnetic wave absorption; moreover, its composite with dielectric materials, that is, the composite of magnetic loss type and electrical loss type electromagnetic wave absorbing materials, enriches the electromagnetic wave absorption mode of the material.
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. Unless otherwise specified, all raw materials used in this invention are commercially available products conventional in the art. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0029] Example 1: A method for preparing a microwave absorbing material composed of a dielectric material with multiple heterogeneous interfaces and iron nitride, such as... Figure 1 As shown, it includes the following steps: Preparation of precursor solution: Dissolve FeCl3·6H2O and urea in 400 ml of ethylene glycol solution, then add nano-silicon carbide powder, and mix evenly by ultrasonic stirring to obtain the precursor solution. In the precursor solution, the concentration of FeCl3·6H2O is 0.02 mol / L, the concentration of urea is 0.1 mol / L, and the concentration of nano-silicon carbide powder is 0.01 mol / L.
[0030] High-temperature reaction in a high-pressure reactor: Pour into a 500 ml reactor, place in a 160 °C oven, and carry out a hydrothermal reaction for 15 h.
[0031] FeOOH / dielectric material composite material was obtained by washing and centrifugation: After the reaction was completed, the pH of the solution after the reaction was measured to be 8.56. The powder obtained from the reaction was washed with alcohol and deionized water and then centrifuged and dried to obtain the FeOOH / dielectric material composite material.
[0032] High-temperature reaction: The powder was placed in a box-type muffle furnace and heat-treated at 500 °C for 1 h to obtain flower-shaped SiC / Fe2O3 composite powder.
[0033] Low-temperature reduction nitriding after tube furnace heat treatment: 0.4 g of flower-shaped SiC / Fe2O3 composite powder and 0.8 g of CaH2 desiccant were mixed and placed in a tube furnace for hydrogen reduction at 400 °C for 2 h under a mixed atmosphere of hydrogen at a flow rate of 300 sccm and argon at a flow rate of 100 sccm. After complete reduction, the powder was protected and cooled under an argon atmosphere and nitrided at 190 °C for 2 h. After nitriding, the powder was cooled to room temperature under an argon atmosphere, and then air and an argon mixture were introduced. The air flow rate was slowly increased and monitored by an oxygen controller, with the oxygen content gradually increased from 0.05% to 5% for pre-oxidation treatment to form a protective oxide layer to prevent the powder from being exposed to air and undergoing severe oxidation. The powder was then dispersed in anhydrous ethanol, and a large amount of unreacted CaH2 was separated by a magnet. Finally, a 1:1 volume ratio mixture of anhydrous ethanol and NH4Cl was used to remove residual CaH2 and its byproducts CaO and Ca(OH)2. After vacuum drying, a self-assembled SiC / iron nitride composite microwave absorbing material with multiple heterogeneous interfaces was obtained, such as... Figure 2 As shown, XRD analysis reveals that its iron nitride phase consists of Fe. 16 The material is composed of N2, Fe4N, and Fe. The microstructure of this microwave absorbing material is shown below. Figure 3 It exhibits a flower-like or sea urchin-like structure. Microscopic morphological elemental analysis reveals... Figure 4 This indicates that SiC and iron nitride are intercalated to form a composite structure. The composite powder was mixed with paraffin wax at a 1:1 mass ratio and pressed into a magnetic ring approximately 2 mm thick using a coaxial mold with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm. The dielectric constant and permeability were measured using a vector grid measuring instrument. The optimal electromagnetic wave absorption was determined using the coaxial method, achieving minimum reflection loss RL at a thickness of 1.5 mm. min The effective absorption bandwidth EAB is -55dB, while the RL is -10dB. max It is 2.84GHz, see Figure 5 (a).
[0034] Example 2: The SiC / Fe2O3 composite powder prepared using the process in Example 1 was mixed with 1g of flower-shaped SiC / Fe2O3 composite powder and 2g of CaH2 desiccant. The mixture was placed in a tube furnace and hydrogen-reduced for 3 hours at 400 °C under a mixed atmosphere of hydrogen at a flow rate of 300 sccm and argon at a flow rate of 100 sccm. After complete reduction, the mixture was protected and cooled under an argon atmosphere, and then nitrided at 190 °C for 4 hours. Following the same nitriding, cooling, pre-oxidation treatment, and desiccant removal followed by vacuum drying as in Example 1, a self-assembled SiC / iron nitride composite microwave absorbing material with multiple heterogeneous interfaces was obtained. The iron nitride phase consisted of Fe... 16 Composed of N2, Fe4N, and Fe3N. Following the steps in Case Study 1, a magnetic ring was fabricated, and its electromagnetic wave absorption performance was tested, achieving RL at a thickness of 1.7 mm. min -61 dB, EAB max It is 2.85GHz, see Figure 5 (b).
[0035] Example 3: 0.02 mol / L Fe(NO3)3·9H2O, 0.2 mol / L urea, and 0.01 mol / L sucrose were dissolved in 400 ml of a 1:1 mixture of ethylene glycol and deionized water, and the mixture was ultrasonically stirred until homogeneous. The solution was poured into a 500 ml reactor and placed in a 150 °C oven for a hydrothermal reaction for 16 h. After the reaction, the pH of the solution was measured to be 8.89. The resulting powder was washed with alcohol and deionized water, then centrifuged and dried. The powder was then heat-treated in a muffle furnace at 500 °C for 30 min to obtain flower-shaped C / Fe2O3 composite powder. 0.6 g of flower-shaped C / Fe2O3 composite powder and 1 g of CaH2 desiccant were mixed and placed in a tube furnace for hydrogen reduction at 400 °C for 3 h under a mixed atmosphere of hydrogen at a flow rate of 200 sccm and argon at a flow rate of 50 sccm. After complete reduction, the mixture was cooled under a protective argon atmosphere and nitrided at 185 °C for 3 h. After nitriding, the same post-nitriding cooling pre-oxidation treatment and desiccant removal followed by vacuum drying were performed as in Case 1 to obtain a self-assembled C / Fe2O3 composite microwave absorbing material with multiple heterogeneous interfaces. The Fe2O3 phase consists of Fe2O3 and Fe2O3. 16 Composed of N2, Fe4N, and Fe3N. The composite powder was mixed with paraffin wax at a mass ratio of 1:1 and pressed into a magnetic ring approximately 2 mm thick using a coaxial mold with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm. The dielectric constant and permeability were measured using a vector grid measuring instrument. The optimal electromagnetic wave absorption was determined using the coaxial method, achieving RL at a thickness of 2.4 mm. min -42dB, EAB max It is 3.91GHz, see Figure 5 (c).
[0036] The microwave absorption properties of the composite materials prepared in the three examples are summarized as follows: Figure 5 (d) indicates excellent wave absorption performance.
[0037] Comparative Example 1: No nano-silicon carbide powder was added to the precursor solution; the subsequent preparation was the same as in Example 1. The final obtained iron nitride phase consisted of Fe... 16 Composed of N2, Fe4N, and Fe, its optimal electromagnetic wave absorption was measured to achieve the minimum reflection loss RL at a thickness of 2.5 mm. min The effective absorption bandwidth is -17.46dB, EAB. max It is 1.272 GHz, see Figure 6 (a).
[0038] Comparative Example 2: No sucrose was added to the precursor solution; the subsequent preparation was the same as in Example 3. The final obtained iron nitride phase consisted of Fe... 16 Composed of N2, Fe4N, and Fe3N, its optimal electromagnetic wave absorption was measured at a minimum reflection loss RLmin of -18.62dB at a thickness of 2.4mm, and an effective absorption bandwidth EABmax of 2.84GHz. (See [reference needed]). Figure 6 (b).
[0039] The microwave absorption performance of the two comparative composite iron nitride preparations was significantly lower than that of Examples 1-3, indicating that the combination of dielectric material and iron nitride can significantly improve the electromagnetic wave absorption performance of the material.
Claims
1. A method for preparing a flower-shaped composite microwave absorbing material with multiple heterogeneous interfaces, characterized in that, Specifically, it includes: Water-soluble iron salts, urea, and dielectric materials are uniformly dispersed in a solvent, and then hydrothermally reacted in a high-pressure reactor to obtain a composite material of iron hydroxyl oxide and dielectric materials. After the reaction, the composite material of iron hydroxyl oxide and dielectric materials is precipitated, centrifuged, dried, and then oxidized by high-temperature heat treatment to obtain a composite precursor powder. The composite precursor is a flower-like structure formed by the interlacing of dielectric materials and iron oxide through hydrothermal reaction. The composite precursor powder was uniformly mixed with a desiccant and fully reduced in a tube furnace under a gas atmosphere. Inert gas was used for protective cooling. The temperature was then lowered to a suitable temperature for low-temperature nitriding. Different composite iron nitrides were prepared by controlling the nitriding conditions. The low-temperature nitriding used an ammonia atmosphere or a mixture of ammonia and hydrogen, with an ammonia flow rate of 100-600 sccm, a hydrogen flow rate of 0-400 sccm, a temperature of 140-200 °C, and a nitriding time of 0.5-40 h. After nitriding, a pre-oxidation treatment is carried out in a low-oxygen atmosphere. Finally, the desiccant and its reaction products are removed, and the material is dried to obtain a composite microwave absorbing material with flower-like multiple heterogeneous interfaces.
2. The preparation method according to claim 1, characterized in that, The water-soluble iron salt is composed of one or two of Fe(NO3)3·9H2O and FeCl3·6H2O mixed in any proportion; the molar ratio of water-soluble iron salt to urea is 1:1~15.
3. The preparation method according to claim 1, characterized in that, The dielectric material is composed of one or two of the following: nano-SiC, carbon powder, or organic sugars that can be dehydrated and carbonized, such as sucrose or glucose, mixed in any proportion. The molar ratio of water-soluble iron salt to dielectric material is 1:0.1~1.
4. The preparation method according to claim 1, characterized in that, The solvent used is ethylene glycol, water, or a mixture of ethylene glycol and water in any proportion, with a volume of 400 ml. The high-pressure reactor has a volume of 500 ml.
5. The preparation method according to claim 1, characterized in that, The hydrothermal reaction temperature is 140~180 °C, and the reaction time is 10~20 h.
6. The preparation method according to claim 1, characterized in that, The high-temperature heat treatment temperature is 300~600 °C, and the reaction time is 0.5~3 h.
7. The preparation method according to claim 1, characterized in that, The nitriding efficiency is improved by using a desiccant to reduce the surface moisture pressure of the powder and increase the ammonia decomposition rate. The desiccant used is CaH2 or CaO, and the mass ratio of iron oxide to desiccant is 1:1~6.
8. The preparation method according to claim 1, characterized in that, The reducing atmosphere uses hydrogen or a mixture of hydrogen and inert gas, with a hydrogen flow rate of 200-600 sccm, an inert gas flow rate of 100-300 sccm, a reduction temperature of 360-420 °C, and a reduction time of 2-4 h.
9. The preparation method according to claim 1, characterized in that, Pre-oxidation forms an oxide film to protect the powder and prevent it from burning due to severe oxidation. The oxygen content in the low-oxygen atmosphere is 5%~60%, and the pre-oxidation time is 20~60 minutes.
10. A composite microwave absorbing material with a flower-like multi-heterogeneous interface, characterized in that, The composite microwave absorbing material with flower-like multi-heteromeric interfaces is prepared by the preparation method described in any one of claims 1-9; the composite material is composed of dielectric material and iron nitride intercalated together, and the overall structure is flower-like with a size of 1-5 μm, wherein the iron nitride contains Fe, Fe2+ ... 16 Composed of two or more of N2, Fe4N, and Fe3N.